Application and research of patent evasion design in automatic connection device. Issue 1 (June 2021) - Zhen-guo, Li; Gong-chang, Ren; Yue-xin, Yang; Le, Wang
Abstract: The patent evasion design may reduce the value of the original patent. In order to avoid this possibility, it is necessary to analyze the development status of the patented technology while conducting the patent evasion design. Combining value analysis with patent evasion methods, a patent evasion design method based on value analysis is proposed. Firstly search related patents by identifying multi-level keywords to obtain the target patent database; then predict and analyze the maturity of the database patents to determine the core patent group; the structure/function model of the core patent is established and its value analysis is analyzed to find the low-value components as the target technology of the circumvention design; next, the contradictory points of the target patent are found through the TRIZ theoretical tool to perform the evasion design, and the new scheme is obtained and the infringement judgment is made. Finally, the method was verified by an automatic connecting device, and the result showed that the improved automatic connecting device has the advantages of simple structure and convenient operation.